2023
DOI: 10.3389/fimmu.2022.1091004
|View full text |Cite
|
Sign up to set email alerts
|

A multi-epitope vaccine GILE against Echinococcus Multilocularis infection in mice

Abstract: IntroductionThe objective of this study is to construct a multi-epitope vaccine GILE containing B-cell and T-cell epitopes against Echinococcus Multilocularis (E. multilocularis) infection based on the dominant epitopes of E. multilocularis EMY162, LAP, and GLUT1.MethodsThe structure and hydrophobicity of GILE were predicted by SWISSMODEL, pyMOL, SOPMA and VMD, and its sequence was optimized by Optimum™ Codon. The GILE gene was inserted into pCzn1 and transformed into Escherichia coli Arctic express competent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“… Immunization with GILE also led to a significant decrease in the maximum diameter and weight of cysts and stimulated the production of CD4 + and CD8 + T Cell. 10 ( Zhou et al, 2023 ) rEM -LAP CFA 10 (i.p.) BALB/C 2000 protoscoleces (i.p.)…”
Section: Resultsmentioning
confidence: 99%
“… Immunization with GILE also led to a significant decrease in the maximum diameter and weight of cysts and stimulated the production of CD4 + and CD8 + T Cell. 10 ( Zhou et al, 2023 ) rEM -LAP CFA 10 (i.p.) BALB/C 2000 protoscoleces (i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, resection of a pulmonary nodule through a laparotomy and transdiaphragmatic approach has also been described in the literature [ 46 ]. Interestingly, accumulating recent research is focused on developing vaccines against E. granulosus and E. multilocularis infections [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…multilocularis infection, and immunization with recombinant proteins of parasites, such as leucine aminopeptidase (LAP), EMY162, EM95 and tetraspanin (TSP), could protect against E . multilocularis infection and infiltration in host livers [22] . A previous study showed that the REMY162 antigen induced a significant level of protection for the host (74.3%) in experimental infection with E .…”
Section: Discussionmentioning
confidence: 99%